2022
DOI: 10.1177/11206721221076701
|View full text |Cite
|
Sign up to set email alerts
|

Do serum vitamin D levels correlate with Macular Edema or with Diabetic Retinopathy?

Abstract: Purpose To compare serum vitamin D (25(OH)D) levels according to the presence of diabetic macular edema (DME) in Diabetes Mellitus (DM) patients with different retinopathy conditions. Methods The files of all DM patients presenting for examination at the ophthalmology clinic between October 2018 and March 2020 were retrospectively examined. Data was collected from the files and included a comprehensive ophthalmological examination, laboratory results from fasting blood tests, and the internal medicine outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Age-related macular degeneration leads to blur or complete loss of central vision. Individuals who suffer from this condition tend to have lower levels of vitamin D than healthy ones [ 40 , 41 , 42 ]. Vitamin D 3 exhibits protective properties against oxidative stress.…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Age-related macular degeneration leads to blur or complete loss of central vision. Individuals who suffer from this condition tend to have lower levels of vitamin D than healthy ones [ 40 , 41 , 42 ]. Vitamin D 3 exhibits protective properties against oxidative stress.…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%
“…This condition is identified by the leakage of retinal vessels, compromised endothelial integrity, and the accumulation of exudative fluid in the macula. The prevalence of DME corresponds with inadequate vitamin D concentrations [ 42 ]. Other results indicate that rectifying vitamin D deficiency (VDD) in DME patients receiving anti-VEGF therapies has a positive impact on sustaining the improvement in visual acuity and reducing central macular thickness observed with these treatments over a period of six months [ 65 ].…”
Section: Diabetic Retinopathy (Dr) and Diabetic Macular Edema (Dme)mentioning
confidence: 99%
“…It has also been suggested that the balance of inflammatory mediators is disrupted in diabetic retinopathy, which results in the production of vascular endothelial growth factors, chemokines, and adhesion molecules that lead to retinal vascular damage 5 , 6 . Moreover, some studies have suggested that vitamin D deficiency is closely associated with diabetic retinopathy 7 , 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that the balance of in ammatory mediators in DR is disrupted, producing vascular endothelial growth factors, chemokines, and adhesion molecules that lead to retinal vascular damage [5,6]. Meanwhile, some studies have suggested that vitamin D de ciency is closely associated with DR [7][8][9].…”
Section: Introductionmentioning
confidence: 99%